Rekonstruksi Laporan Keuangan Masjid Jami’ Darussalam Glenmore Berdasarkan PSAK No.109 - Fian Handayani; Yulinartati Yulinartati; Diyah Probowulan (Universitas Pendidikan Ganesha, 2020)
The Institute of Indonesia Chartered (IAI) has issued financial accounting standards in regard to financial statements of zakat, infaq / sadaqah. The standard is included in Statement of Financial Accounting Standards Number 109 (Revised 2011) concerning on financial statement of zakat, infaq / sadaqah. This research is conducted at the Jami 'Darussaalam Mosque Glenmore in order to reconstruct the financial statements of zakat, infaq / sadaqah, thus it can be used to consider the financial statements of the Jami Darussalam Mosque in accordance with PSAK No.109 for Takmir or mosque management. This research uses a descriptive method which is conducted by observation, documentation and direct interviews with the secretary and deputy treasurer of the Takmir's Jami' Darussalam Mosque. This research is intended to describe certain conditions and symptoms in detail that occur at the Jami 'Darussaalam Glenmore Mosque, and to provide an overview of the financial statements of zakat, infaq / sadaqah of the mosque which then reconstruct the financial statements of zakat, infaq / sadaqah of the Jami' Darussalam Glenmore Mosque in accordance with applicable standards, which is PSAK No.109. Transparency and accountability on financial statement of zakat, infaq / sadaqah are completed based on PSAK 109, which consists of five components of financial statements, those are the statement of financial position, changes in fund statements, managed assets, cash flow statements, and financial statements.